Comparing User Experience Maxim and inDrive Applications Using the User Experience Questionnaire - Fauzi Adi Saputra; Mia Putri Yeza; Muhammad Farhan Fahrezy; Amata Fami; Irma Rasita Gloria Barus (Lembaga Penelitian dan Pengabdian Masyarakat, 2024)
Online transportation applications are vital in meeting daily mobility needs in today's world. The fierce competition between transportation apps like Maxim and Indrive demands a deep understanding of user satisfaction factors to ensure preference and loyalty. This study aims to recognize and compare elements that impact user satisfaction of the two applications. User satisfaction with both applications. Using the quantitative method of data for the User Experience Questionnaire (UEQ) was gathered via an online survey. from 89 respondents. These questionnaires are designed to measure specific aspects of the user experience. The data analysis findings indicate that Maxim achieved a superior user experience score over InDrive because it excelled in attractiveness, perspicuity, efficiency, dependability, stimulation, and novelty. These findings indicate that service availability and the quality of user interaction with the application determine user satisfaction. The conclusion of this study emphasizes the importance of understanding user preferences and providing services that meet their needs and offer a superior user experience. These results can potentially guide the development of strategies to increase user satisfaction and loyalty in the ride-hailing industry.